Miss AI on Instagram: Virtual Influencers Representation in Beauty Pageants - Mata-Núñez, Almudena; Villén-Higueras, Sergio Jesús (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The first beauty pageant for virtual influencers created with generative artificial intelligence emerged in 2024. In this context, the main objective of this research is to analyze the image and representation of said competition’s participants on Instagram. Adopting a quantitative and qualitative methodology, 50 posts (966 images) on Instagram from the ten WAICA 2024 finalists are analyzed. For this process, an analysis template created for this study is used. Among the main results, it is obtained that the candidates perpetuate the feminine beauty ideal that reproduces patriarchal standards and bases their identity essentially on the image of the self.